Psoralis mirnae sp. nov., the first species of the skipper genus from Central America (Lepidoptera: Hesperiidae) - Siewert, Ricardo Russo; Nakamura, Ichiro; Mielke, Olaf Hermann Hendrik (Zootaxa, 2014)
Psoralis Mabille, 1904 (Hesperiinae: Moncini) contains 11 species of skippers distributed throughout South America (Mielke 2004, 2005). According to Evans (1955), Psoralis resembles Lerema Scudder, 1872, in several morphological characters of antennae, palpi, wings and legs, but could be distinguished from the latter by the male genitalia, where the uncus is undivided instead of being quadrifid. This paper describes a new species of Psoralis from Central America, P. mirnae sp. nov., based on specimens collected by the second author (I. Nakamura) in Guatemala.